1970
DOI: 10.3329/bjms.v10i3.8361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal anaemia on neonatal outcome – a study done in the specialized urban hospital set up in Bangladesh

Abstract: Context: Anaemia is a common pregnancy related disorder in Bangladesh that causes various maternal and fetal problems. A prospective study was designed to see the associated maternal factors and fetal outcome in different categories of anaemia and to compare with that of normal pregnancy. Methods: The study was carried out on 60 Bangladeshi women within 35-40 weeks of gestation. Among them, 20 with normal uncomplicated pregnancies were considered as control group or group A, another 27 having pregnancies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
2
0
2
Order By: Relevance
“…In agreement with this study, Rani et al [14] found that poor APGAR score (taken as score less than 7 at 5 minutes), early neonatal death and NICU admission were higher in anemic group than non-anemic group and it was statistically significant. This is in agreement with many studies [15,16] .…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with this study, Rani et al [14] found that poor APGAR score (taken as score less than 7 at 5 minutes), early neonatal death and NICU admission were higher in anemic group than non-anemic group and it was statistically significant. This is in agreement with many studies [15,16] .…”
Section: Discussionsupporting
confidence: 94%
“…7 According to Mahamuda et al there is significant difference in apgar score of infants born to anaemic and non anaemic mothers. 8 Hooton et al stated that the relationship of anaemia and infections may be due to adverse effect on immune function, by altering the proliferation of T and B lymphocytes, reducing the bactericidal activity of phagocytes and neutrophils. 9 Consequently the complication of preterm labour and pregnancy related infections has also been shown to have a causal relationship with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Riffat Jalil et al studied on 51 pregnant women admitted for delivery & compared with 108 non-anemic women of similar features & found that frequency of anemia was 69.9% and severe anemia was 4.8% [28]. B. Mahamuda et al observed in her study that mild, moderate & severe anemia was 45%, 21.67% & none respectively [29].…”
Section: © 2018 Akbar T Et Al This Article Is Distributed Under Thementioning
confidence: 99%